Intellectual Capital and Financial Sustainability - I Gede Cahyadi Putra; Ni Luh Putu Wiagustini; I Wayan Ramantha; Ida Bagus Panji Sedana (AIBPM Publisher, 2022)
Â The competition among companies in the industrial era 4.0 no longer relies on ownership of tangible assets but on the ability to control information, develop innovation, manage organizations and own resources. Companies increasingly emphasize the importance of knowledge assets to improve their performance and sustainability. The purpose of this study is to figure out the effect of intellectual capital, consisting of human capital, structural capital and relational capital on marketing performance, financial strategy performance and financial sustainability. The research was conducted in rural banks, which also known as Bank Perkeditan Rakyat (BPR) operating in Bali. The data analysis technique used SEM PLS. The results showed that human capital and relational capital positively effects marketing performance, financial strategy performance and financial sustainability. Meanwhile, the relational capital variable does not have effect on financial strategy performance and financial sustainability.Â Keywords: Financial Strategy Performance, Financial Sustainability, Intellectual Capital, Marketing Performance, Rural Bank